Selective Exposure, Media Trust and Party Identification - So, Kwok Wai. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Economics.; Advisor: Enrico Spolaore.; Committee: Marcelo Bianconi.; Keyword: Economics.